АКРОБАТИКА МАШҚЛАРИНИ РИВОЖЛАНТИРИШ УСЛУБИЯТИ - Ешбаев, А.Ж.; Утениязова, Ш.Б. (SCIENCE and SOCIETY, 2024)
This article describes the biomechanical analysis of acrobatic exercises. The structure of the motor action of athletes, the “school” of movements, is justified. The significance of “special technical training” is determined in the General system of training young acrobats – jumpers, the direction of improving the technique of competitive exercises for years of training.
Keywords: technical training; “school” of movements; coordination of movements; artistry; statistics; biomechanics of movements